About the article Morphology of echinococcal liver lesions during treatment with high-intensity focused ultrasound - Diego Sebastián Andrade Mora; Stalin Santiago Celi Simbaña (National Scientific Medical Center, 2022)
The authors, after reading the article entitled "Morphology of echinococcal liver lesions during treatment with high-intensity focused ultrasound", published in the Journal of clinical medicine of Kazakhstan, were motivated to address the editorial team and the general public to refer their considerations about.